Introducing a Thermo-Alkali-Stable, Metallic Ion-Tolerant Laccase Purified From White Rot Fungus Trametes hirsuta - Si, Jing; Ma, Hongfei; Cao, Yongjia; Cui, Baokai; Dai, Yucheng (Frontiers in Microbiology, 2021)
This study introduces a valuable laccase, designated ThLacc-S, purified from white rot fungus Trametes hirsuta. ThLacc-S is a monomeric protein in nature with a molecular weight of 57.0 kDa and can efficiently metabolize endocrine disrupting chemicals. The enzyme was successfully purified to homogeneity via three consecutive steps consisting of salt precipitation and column chromatography, resulting in a 20.76-fold increase in purity and 46.79% yield, with specific activity of 22.111 U/mg protein. ThLacc-S was deciphered as a novel member of the laccase family and is a rare metalloenzyme that contains cysteine, serine, histidine, and tyrosine residues in its catalytic site, and follows Michaelis-Menten kinetic behavior with a Km and a kcat/Km of 87.466 μM and 1.479 s–1μM–1, respectively. ThLacc-S exerted excellent thermo-alkali stability, since it was markedly active after a 2-h incubation at temperatures ranging from 20 to 70°C and retained more than 50% of its activity after incubation for 72 h in a broad pH range of 5.0–10.0. Enzymatic activities of ThLacc-S were enhanced and preserved when exposed to metallic ions, surfactants, and organic solvents, rendering this novel enzyme of interest as a green catalyst for versatile biotechnological and industrial applications that require these singularities of laccases, particularly biodegradation and bioremediation of environmental pollutants.